The Role of Madrasah Heads as Academic Supervisors in Improving Teachers' Pedagogic Competencies - Lia Nurhayati; Priyo Susilo (Journal La Edusci, 2022)
A teacher must not only be excellent at teaching, but also have a wide knowledge base, be smart, and be able to interact with students effectively. Pedagogic competence, social competence, personality competence, and professional competence are the four qualities that teachers must demonstrate in order to be effective in their roles. The teaching profession is a unique sphere of employment that necessitates the use of professional standards. Madrasah Ibtidaiyah Al-Khairat is one of the several Madrasas that operate under the auspices of the Ministry of Religion of the North Bolaang Mongondow Regency. It is located in the village of Ibtidaiyah Al-Khairat. Faculty members' professional talents are intended to be improved via academic supervision provided by the madrasah's administrator.